Global and regional estimates of prevalence of refractive errors: Systematic review and meta-analysis - Hashemi, Hassan (J Curr Ophthalmol, 2017)
PURPOSE: The aim of the study was a systematic review of refractive errors across the world according to the WHO regions. METHODS: To extract articles on the prevalence of refractive errors for this meta-analysis, international databases were searched from 1990 to 2016. The results of the retrieved studies were merged using a random effect model and reported as estimated pool prevalence (EPP) with 95% confidence interval (CI). RESULTS: In children, the EPP of myopia, hyperopia, and astigmatism was 11.7% (95% CI: 10.5–13.0), 4.6% (95% CI: 3.9–5.2), and 14.9% (95% CI: 12.7–17.1), respectively. The EPP of myopia ranged from 4.9% (95% CI: 1.6–8.1) in South–East Asia to 18.2% (95% CI: 10.9–25.5) in the Western Pacific region, the EPP of hyperopia ranged from 2.2% (95% CI: 1.2–3.3) in South-East Asia to 14.3% (95% CI: 13.4–15.2) in the Americas, and the EPP of astigmatism ranged from 9.8% in South-East Asia to 27.2% in the Americas. In adults, the EPP of myopia, hyperopia, and astigmatism was 26.5% (95% CI: 23.4–29.6), 30.9% (95% CI: 26.2–35.6), and 40.4% (95% CI: 34.3–46.6), respectively. The EPP of myopia ranged from 16.2% (95% CI: 15.6–16.8) in the Americas to 32.9% (95% CI: 25.1–40.7) in South-East Asia, the EPP of hyperopia ranged from 23.1% (95% CI: 6.1%–40.2%) in Europe to 38.6% (95% CI: 22.4–54.8) in Africa and 37.2% (95% CI: 25.3–49) in the Americas, and the EPP of astigmatism ranged from 11.4% (95% CI: 2.1–20.7) in Africa to 45.6% (95% CI: 44.1–47.1) in the Americas and 44.8% (95% CI: 36.6–53.1) in South-East Asia. The results of meta-regression showed that the prevalence of myopia increased from 1993 (10.4%) to 2016 (34.2%) (P = 0.097). CONCLUSION: This report showed that astigmatism was the most common refractive errors in children and adults followed by hyperopia and myopia. The highest prevalence of myopia and astigmatism was seen in South-East Asian adults. The highest prevalence of hyperopia in children and adults was seen in the Americas.